Hybrid methodology using balancing optimization and vibration analysis to suppress vibrations in a double crank-rocker engine - Albaghdadi, A.M. (Polish Academy of Sciences Branch Lublin, 2022)
This study aims to present mathematical modelling to evaluate and analyze double crank-rocker engine performance. The study suggests the use of two methods to reduce system vibration through balancing optimization and vibrational analysis. The combination of both methods acts as a verification method; besides it can be used as a tool for further system design enhancement and condition monitoring. The derived mathematical model is then used for balancing optimization to identify system shaking forces and moments, while variable speed is considered as an added parameter to evolve the optimization process. This factor shows better enhancement in reducing system shaking forces and moments compared to constant speed balancing method. Next, the system characteristics were concluded in terms of mode shapes and natural frequencies using modal and frequency response analysis, which give clear clue for secure system operational ground. Finally, the reduction in system vibrations was translated into engineâs centre of mass velocity, which evaluates balancing process effectiveness and indicate if further enhancement should be conducted. Â© 2022, Polish Academy of Sciences Branch Lublin. All rights reserved.